Estetika Visual Kriya Keramik Berornamen Wayang Khas Bali - I Wayan Mudra; I Gede Mugi Raharja; I Wayan Sukarya (Gondang: Jurnal Seni dan Budaya, 2021)
The Balinese puppets in the traditional paintings as a cultural heritage has inspired Balinese craftsmen created ceramic works of aesthetic value. The efforts these craftsmen can be read as resistance to entry the ceramic works from outside and the production of the ceramic art in Indonesia that ignore Indonesian characters. This study aims to discuss the aesthetics of visuals ceramic works that apply Balinese puppets ornaments. The data collection method by observation and documentation. The results showed that the aesthetics of the ceramic craft products with Balinese puppets ornaments seen from unity, harmony, symmetry, balance, and contrast are quite good, although not yet optimal. Besides, the visual aesthetics of the ceramic works have not displayed good complexity, so the beauty that obtained was not optimal. The visual aesthetic assessment of this work was subjective in nature, so it was possible that there will be different judgments. The conclusion that aesthetics can be achieved by elevating the cultural traditions of the past and at the same time as a form of appreciation for that culture and become a differentiator amid the rise of Chinese ceramics in Indonesia.